2007
DOI: 10.1002/chem.200600965
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Influence on Connectivity and Processing: Magnetic Crystals Based on Metalloceniums and Films of TCNE‐Based Magnets (TCNE=Tetracyanoethylene)

Abstract: Molecular materials built from coordination complexes exhibit properties that can be explained through intermolecular electronic interactions driven by the ligand moieties. The nature of the ligand in the precursor molecules governs the connectivity of the magnetic phases and the possibility of producing them by using a gas-phase process. Metallocenium, metal bisdithiolate materials, and solvated and solvent-free [M(tcne)2] (tcne=tetracyanoethylene) magnets illustrate such features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
(66 reference statements)
4
11
0
Order By: Relevance
“…This three-dimensional ͑3D͒ molecular-based material is a soft magnet with low coercive field 7,11 and exhibits roomtemperature semiconducting behavior with a thermal activation energy of 0.5 eV. 12,13 Studies based on x-ray absorption near-edge spectroscopy ͑XANES͒ and XPS measurements have suggested that the oxidation state of V is near +2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This three-dimensional ͑3D͒ molecular-based material is a soft magnet with low coercive field 7,11 and exhibits roomtemperature semiconducting behavior with a thermal activation energy of 0.5 eV. 12,13 Studies based on x-ray absorption near-edge spectroscopy ͑XANES͒ and XPS measurements have suggested that the oxidation state of V is near +2.…”
Section: Introductionmentioning
confidence: 99%
“…However, the commercial use of V͑TCNE͒ 2 is currently limited as the material is amorphous and extremely air and water sensitive. 3,6,7,10,11 The lack of long-range order and the substantial influence of the synthetic procedure ͑i.e., starting materials, 3,25 solvent, 9 and preparation method 6,7,26,27 ͒ on the system properties clearly suggest that V͑TCNE͒ 2 compounds contain structural defects and impurities such as residual solvent and/or by-products. Furthermore, it is possible that multiple metastable structures are thermodynamically feasible under typical preparation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Development of chemical vapor deposition (CVD) fabrication techniques has however improved stability and reproducibility of the material [13][14][15][16][17]. An extended x-ray absorption fine structure (EXAFS) study has probed the local structure of the compound, showing that the vanadium ion coordinates to about six nitrogen atoms, most likely in a slightly distorted octahedral environment, each with an average distance in room temperature of 2.084(5) Å [18].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] The high Curie temperature in combination with semiconducting behavior and complete spin polarization 7 makes V͑TCNE͒ x a promising material for spintronic applications. 8 A main problem of V͑TCNE͒ x , however, is its extreme air sensitivity 2,[9][10][11]13 and that residual solvent molecules and/or precursor-based by-products negatively affect magnetic properties 11,14 as well as introduce electron trap states. 15 Here, we present a in situ preparation method based on physical vapor deposition ͑PVD͒ resulting in films free from residual solvent molecules and precursor-based byproducts.…”
mentioning
confidence: 99%
“…The coercive field obtained is ϳ65 Oe, which is higher than expected for defect-rich CVD-prepared V͑TCNE͒ x but similar to what is obtained for relatively defect-free CVDprepared V͑TCNE͒ x . 11 The temperature dependence ͑zero field cooled͒ of the magnetization at an applied file of 20 Oe is depicted in Fig. 3͑b͒.…”
mentioning
confidence: 99%